Zeitschrift für Antikes Christentum / Journal of Ancient Christianity (De Gruyter, 1997)
The Journal of Ancient Christianity is a peer-reviewed academic journal which aims at encouraging the dialogue between scholars of church history, history of religion, and classical antiquity with all its subdisciplines.